(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تتشكل الدوامات البحرية على طول الشاطئ السوري نتيجة اضطراب الجريان الشاطئي AW (Atlantic Water : مياه الأطلسي التي تدخل إلى البحر الأبيض المتوسط عبر مضيق جبل طارق ضمن الطبقة السطحية). اعتمدت بعض الدراسات المرجعية لوصف هذه الدوامات على تحليل الصور الفضائية من النوع SST (Sea Surface Temperature)، فتبين أنها عابرة وأنتيسيكلونية. أظهر تحليل الصور الفضائية في هذا البحث دوامة سيكلونية محصورة بين خطي العرض 34.5 °N و 35.5 °N على طول الشاطئ السوري، كما حُددت مواصفاتها حيث وصل قطرها إلى 100 km تقريباً أما زمن حياتها فلم يتجاوز ثلاثة الأشهر. The eddies at the Syrian coast are generated by the instability of the alongshore surface circulation (AW: Atlantic Water which enters the Mediterranean Sea by Gibraltar). These eddies have been almost described as transitory and anticyclonic by analyzing the infrared satellite images (SST: Sea Surface Temperature) looking at some bibliographic studies. Our analysis of the Satellite images inferred a cyclonic eddy between 34.5 °N and 35.5 °N at the Syrian coast. This eddy`s diameter arrived at 100 km while its lifetime was three months.